Evaluation of the Quantum II yeast identification system. - Kiehn, T E (1985)
We compared three methods for identifying clinical yeast isolates: Abbott Quantum II, API 20C, and a modified BBL Minitek system. The API 20C and modified Minitek systems agreed on the identification of 243 of 245 yeasts (99.2%). The Quantum II system correctly identified 197 (80.4%), incorrectly identified 19 (7.8%), and did not identify 29 (11.8%) of the yeasts. Most of the misidentifications with the Quantum II occurred because assimilation or biochemical results were false-positive. Sixteen different species of yeasts and 16 different Quantum II substrates contributed to the discrepancies. On retesting with the Quantum II, 31% of the discrepant strains were correctly identified, while the remaining 69% were incorrectly identified or were not identified. Erroneous biochemical and assimilation results were also noted with yeasts that were correctly identified by the Quantum II system.